2022
DOI: 10.1111/faf.12648
|View full text |Cite
|
Sign up to set email alerts
|

Global assessment of shark strandings

Abstract: Marine wildlife stranding is a global phenomenon that affects both invertebrates and vertebrates (Chan et al., 2017;Cockcroft, 2001). Many definitions are available, being guided mostly by the taxonomic group affected. The National Oceanic and Atmospheric Administration (NOAA) recognizes three main taxonomical categories of strandings: cetaceans, pinnipeds and sea turtles. Stranded animals may be found dead (either on land or floating) or alive but unable to return to sea due to injury or illness. Broader defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Reports from citizen scientists on social media have helped determine both the spatial and temporal distribution of cetacean strandings (Ortiz-Wolford et al 2021). Although most efforts using citizen science websites or social media to report marine animal strandings seem to focus on charismatic megafauna (Mwango'mbe et al 2021, Ortiz-Wolford et al 2021, Wosnick et al 2022) the implications for conservation in other species should not be overlooked. Much of the citizen science data collected on marine bird strandings consists of volunteer, standardized beach surveys (Parrish 2009, Piatt et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Reports from citizen scientists on social media have helped determine both the spatial and temporal distribution of cetacean strandings (Ortiz-Wolford et al 2021). Although most efforts using citizen science websites or social media to report marine animal strandings seem to focus on charismatic megafauna (Mwango'mbe et al 2021, Ortiz-Wolford et al 2021, Wosnick et al 2022) the implications for conservation in other species should not be overlooked. Much of the citizen science data collected on marine bird strandings consists of volunteer, standardized beach surveys (Parrish 2009, Piatt et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gonçalves e Silva et al (2020) , observed that G. altavela individuals living in natural environments contained specific bacteria and postulated positive health effects due to this microorganism/host interaction. Temperature appears to be the environmental variable most related to the proliferation of infectious agents in marine animals, and abrupt water temperature alterations are a significant source of mortality associated with infections in stranded sharks ( Wosnick et al, 2022 ). In a climate change scenario, this is of particular concern, as an increase in potentially lethal infectious diseases is expected, as well as pathogens associated with sublethal outcomes, such as reduced immune response, physical condition, and fitness which, in turn, can directly affect population recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Marine predators such as sharks and rays using intertidal habitats are faced with an additional risk: the risk of stranding upon tidal flat emergence with the receding tide (Brinton & Curran, 2017; Campos et al, 2009). When the receding tide sets in, the stranding risk for sharks and rays seeking refuge or feeding in intertidal habitats increases (Figure 3c) (Wosnick et al, 2022). Sharks feeding in intertidal habitats are thought to limit use of the intertidal until the incoming tide reaches its highest levels, leaving the intertidal as soon as the tide starts to recede, possibly by sensing barometric changes (Campos et al, 2009; Rasher et al, 2017).…”
Section: Intertidal Habitat Use By Sharks and Raysmentioning
confidence: 99%
“…Marine predators such as sharks and rays using intertidal habitats are faced with an additional risk: the risk of stranding upon tidal flat emergence with the receding tide (Brinton & Curran, 2017;Campos et al, 2009). When the receding tide sets in, the stranding risk for sharks and rays seeking refuge or feeding in intertidal habitats increases (Figure 3c) (Wosnick et al, 2022). Sharks feeding in intertidal…”
Section: Stranding Risk Effects and Avoidancementioning
confidence: 99%
See 1 more Smart Citation